Exploring the Challenges of implementing the American English Language Curriculum in the Middle and High Schools of the International Schools in the United Arab Emirates - Wahb, Murhaf (2020)
This research aims to explore the challenges of the American English curriculum and its implemntation in both middle and high schools in the international schools in the United Arab Emirates. Moreover, the researcher seeks the possible ways to overcome challenges of the American English curriculum, explores the benefits of learning, and the ways to assess the students concerning the American English curriculum highlighting the significance of this curriculum to improve the students’ proficiency in the four areas of language reading, listening, speaking and writing. In addition, the aim here is to show the role of the English teachers’ knowledge and competency in impmenting the curriculum sharing their best practices in oder to deliver a quality learning to their students. The tools used to gather information for this research are a detailed interview (qualitative measure) with a school principal and questionnaires (survey – quantitative measure) to highlight the opinions of both middle and high school teachers to develop answers to the research questions. Based on the analysis of the mixed-methodolgy of gathering data, the research findings show that the role of teachers is considered of a paramount importance as they are known the main role players in teaching students and in implementing the curriculum. Moreover, the research study also provides pieces of evidence that teachers’ support, collaboration and communication must be improved, and finally, the application of 4Cs of the 21 century skills are part and parcel of this curriculum to evaluate and to assess students’ real-life knowledge and to improve the quality of learning.